Pengaruh model pembelajaran problem based learning terhadap hasil belajar IPAS siswa di kelas IV SD Kepuhan Bantul - Lestari, Devi; Utaminingsih, Retno; Murniningsih, Murniningsih (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to: 1) determine the trend of science and science learning outcomes for fourth grade students at Kepuhan Bantul Elementary School whose learning uses the Problem Based Learning (PBL) model, 2) determine the tendency for science and science learning outcomes for fourth grade students at Kepuhan Bantul Elementary School whose learning uses a direct model, and 3 ) to find out the differences in science and science learning outcomes for fourth grade students at Kepuhan Bantul Elementary School using the Problem Based Learning (PBL) model and the direct model. This type of research is a quasi experiment with Nonequivalent Control Group Design. Data collection techniques use documentation, observation and tests. Data analysis techniques use descriptive analysis, initial t test, and analysis prerequisite tests consisting of normality tests, homogeneity tests, and hypothesis tests. The research results show that: 1) the learning outcomes of the experimental class using the Problem Based Learning (PBL) learning model tend to be very high; 2) the learning outcomes of the control class using the direct model have a high tendency; 3) In the t-test obtained (P = 0.010 < 0.05), the hypothesis is accepted, meaning there is a significant difference in science learning outcomes between the experimental and control classes. The average learning outcomes of the class with the Problem Based Learning (PBL) learning model obtained a score of 15 higher than the average of the direct learning model class which obtained a score of 12.57 so that there is an influence of the Problem Based Learning (PBL) learning model on the science and science learning outcomes of class IV students at Kepuhan Elementary School, Bantul.. Keywords: Learning model; Problem Based Learning; Learning outcomes; IPAS